2012
DOI: 10.5414/cn107570
|View full text |Cite
|
Sign up to set email alerts
|

Changes in peritoneal membrane permeability and proteinuria in patients on peritoneal dialysis after treatment with paricalcitol – a preliminary study

Abstract: The results of the study indicate that paricalcitol is effective in treating hyperparathyroidism in patients on PD, and suggest an effect upon proteinuria and PM permeability (not previously reported), with diminished peritoneal protein loss and increased ultrafiltration. The antiinflammatory, antifibrotic and RAAS-modulating actions described for paricalcitol may be responsible for these findings, and could be important for preserving the peritoneum as a dialyzing membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Several studies have previously investigated the protective effect of vitamin D on peritoneal membranes. Coronel et al reported a preliminary study showing that paricalcitol decreased peritoneal membrane permeability, with diminished peritoneal protein loss and increased ultrafiltration in PD patients [ 23 ]. Lee et al proved that calcitriol could decrease peritoneal fibrosis in a rat model of acute CG exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have previously investigated the protective effect of vitamin D on peritoneal membranes. Coronel et al reported a preliminary study showing that paricalcitol decreased peritoneal membrane permeability, with diminished peritoneal protein loss and increased ultrafiltration in PD patients [ 23 ]. Lee et al proved that calcitriol could decrease peritoneal fibrosis in a rat model of acute CG exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have proven a protective effect of vitamin D against peritoneal fibrosis [ 23 27 ]. Furthermore, studies in the field of cancer research also found that vitamin D can ameliorate cancer cell EMT through the promotion of E-cadherin expression [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective study, which included 23 patients on PD medicated with paricalcitol, with a mean dose of 1.3 µg/day and a follow-up period of 3 ± 2 months (range 2–5), Coronel et al [15] reported a decrease in PPL from 0.91 ± 0.35 to 0.76 ± 0.26 g/L (15.4%; p = 0.007) and from 7.55 to 6.46 g/24 h ( p < 0.033). In the control group, which included 15 patients not receiving any form of vitamin D, no changes in peritoneal membrane permeability were found.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the usefulness in the treatment of hyperparathyroidism, the VDR activators have shown anti-inflammatory pleiotropic effects [11], antifibrotic properties [12] and inhibitory actions upon the renin angiotensin aldosterone system (RAAS) [13], demonstrating antiproteinuric action in patients with CKD [14]. The role of VDR activators in reduction of PPL has recently been a subject of interest; however, the results are controversial [15, 16]. The aim of this study was to analyze the relationship between therapy with paricalcitol and PPL in a cohort of PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, paricalcitol was associated with lower risk of hospitalization in those patients with more severe LVH [83]. Of note, paricalcitol resulted associated with significant reduction of oxidative stress [84] and improved peritoneal membrane permeability in hemodialysis and peritoneal dialysis, respectively [85]. However, no RCTs have tested the effect of paricalcitol against other forms of vitamin D on albuminuria and LVH.…”
Section: Vdra: a Multifaceted Choice From Secondary Hyperparathyromentioning
confidence: 99%